Perbandingan Efektivitas Terapi Akupresur dan Aromaterapi Lemon Terhadap Dismenore Pada Remaja Putri - Geni Ranjani (HEALTH CARE: JURNAL KESEHATAN, 2023)
Introduction: Dysmenorrhea is pain that occurs during menstruation due to an imbalance in the production of prostaglandin in the blood, resulting in very severe pain that often occurs in women during menstruation. Objective: This study aims to compare the effectiveness of acupressure and lemon aromatherapy on dysmenorrhea in adolescent girls at the Faculty of Nursing, University of Riau. Methods: This study uses a quasi-experimental method with a pretest-posttest design without a control group. The sample used was 34 respondents which were taken based on inclusion criteria with purposive sampling technique. The measuring instrument used is an observation sheet using a Numeric Rating Scale. Results: The results of univariate analysis showed that the majority of respondents were at the age of 20 years as many (44.1%). The results of the bivariate analysis in this study using the independent T test obtained p value 0,420 > (0,05), so there was no significant difference between the acupressure group and the lemon aromatherapy group. The average comparison of pain intensity before and after acupressure and lemon aromatherapy where in the lemon aromatherapy group was 2.06 while the acupressure group was only 1.53. Conclusion: Acupressure and lemon aromatherapy are effective in reducing dysmenorrhea pain, but there is no significant difference between the two groups so that both are recommended to be used to reduce dysmenorrhea pain. Suggestion: Acupressure and lemon aromatherapy can be chosen either or both because they are proven to be equally effective in overcoming dysmenorrhea.